Use of Computer Simulation in Dental Training with Special Reference to Simodont - Angie Lok-Sze Leung; Conson Yeung; Samantha Chu; Amy Wai-Yee Wong; Ollie Yiru Yu; Chun-Hung Chu (MDPI AG, 2021)
Simulation-based dental education has been increasingly implemented in dental training. Virtual reality simulators are being explored as an adjunct to dental education. Simulation-based dental education could serve as a powerful aid to preclinical instruction. This article provides an overview of how dental simulators can be used in dental instruction and manual dexterity training, utilizing the Simodont dental trainer as a reference. The Simodont dental trainer provides a platform for students to hone their manual dexterity skills and practice repeatedly prior to conventional clinical simulations. Additionally, it can reduce resource wastage. However, the financial cost of setting up and maintaining the system can be high. The high cost would ultimately limit the number of devices each individual school could afford, as a potential drawback to meeting the training needs of many dental students at one time. The machine's force-feedback mechanism provides trainees with the tactile experience of drilling into various tissues. Students are empowered via self-learning and assessment, with guidance provided for diagnosis and treatment. From training students on basic operative skills to providing basic aptitude tests for entrance examinations, the Simodont dental trainer's functions and potential for further development may make it a valuable tool in the field of simulation-based dental education.